2012
DOI: 10.1186/1751-0147-54-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pneumonia in calves after experimental infection with Mycoplasma bovis strain 1067: Characterization of lung pathology, persistence of variable surface protein antigens and local immune response

Abstract: BackgroundMycoplasma bovis is associated with pneumonia in calves characterized by the development of chronic caseonecrotic lesions with the agent persisting within the lesion. The purposes of this study were to characterize the morphology of lung lesions, examine the presence of M. bovis variable surface protein (Vsp) antigens and study the local immune responses in calves after infection with M. bovis strain 1067.MethodsLung tissue samples from eight calves euthanased three weeks after experimental infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 41 publications
7
42
0
1
Order By: Relevance
“…Interestingly, whereas IL-10 is known to impair the antigen-presenting capacity of monocytes and macrophages through decreased expression levels of surface major histocompatibility complex class II (MHC-II) and other costimulatory molecules, in our case, M. bovis-infected monocytes exhibited enhanced expression of MHC-II molecules (data not shown). Some reports have demonstrated that M. bovis preferentially induces a host Th2 immunological response characterized by strong IgG1 responses that do not confer protection in experimental vaccines (6,7). The absence of IFN-␥ and TNF-␣ from M. bovis-infected monocytes agrees with those observations.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Interestingly, whereas IL-10 is known to impair the antigen-presenting capacity of monocytes and macrophages through decreased expression levels of surface major histocompatibility complex class II (MHC-II) and other costimulatory molecules, in our case, M. bovis-infected monocytes exhibited enhanced expression of MHC-II molecules (data not shown). Some reports have demonstrated that M. bovis preferentially induces a host Th2 immunological response characterized by strong IgG1 responses that do not confer protection in experimental vaccines (6,7). The absence of IFN-␥ and TNF-␣ from M. bovis-infected monocytes agrees with those observations.…”
Section: Discussionsupporting
confidence: 79%
“…Observations from experimentally infected cattle have revealed stimulation of both innate and adaptive immunity (5,6). The pulmonary bovine immune response to M. bovis is mainly anti-inflammatory, with high levels of interleukin-4 (IL-4) and moderate levels of gamma interferon (IFN-␥) and IgG1 antibodies (6,7). Although M. bovis infects predominantly mucosal and serosal surfaces, live bacteria can be detected in brain of infected cattle (8).…”
mentioning
confidence: 99%
“…In the lung, M. bovis produces chronic bronchopneumonia characterized by caseonecrotic nodules in the cranioventral lung lobes (2,10,24). Microscopic findings suggest that lung necrosis is originated in small bronchi and bronchioles (15,18). The persistence of the agent in the lung tissue and the chronicity of the pulmonary lesions imply that the immune response is ineffective in eliminating the infection (6,18,21).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, M. bovis is not the only bacteria isolated from pneumonic lung lesions, and the presence of M. bovis antibody is not always associated with successful culture of M. bovis. This suggests that M. bovis alone may not always be the cause of BRD, but in some way may predispose animals to LRT colonisation by other bacteria, which are also often commensals of the URT, leading to the development of BRD (Gourlay and Houghton, 1985, Hermeyer et al, 2012.…”
Section: Brd50 and Sero-conversion To M Bovis Or A Sero-increase In mentioning
confidence: 99%
“…Experimental infection trials conducted using calves have shown that M. bovis has both stimulating and suppressing effects on the bovine immune response (Hermeyer et al, 2012). The production of nitric oxide and tumor necrosis factor-alpha by macrophages is stimulated (Jungi et al, 1996); apoptosis of lymphocytes (Vanden Bush and Rosenbusch, 2002) and the production of a lympho-inhibitory peptide is induced (Vanden Bush and Rosenbusch, 2004); while lymphocyte responses to mitogens and the neutrophil oxidative burst is suppressed (Wiggins et al, 2010).…”
Section: Brd50 and Sero-conversion To M Bovis Or A Sero-increase In mentioning
confidence: 99%